Why do research into men's care work? - Hrženjak, Majda (Teorija in praksa, 2019)
In this article that introduces this special section, the authors place research about men's involvement in care work in the broader context of gender, welfare system and social policy studies as well as in the sociology of work. The main theoretical approaches in researching the gender division of care are presented, with a special consideration of the male perspective as conceptualised in critical studies of men and masculinities. The discussed topical reflections and empirical evidence concerning men's inclusion in formal and informal care work in Europe reveal that men's increasing share of care may be seen as a counterpart to the traditional concepts of male power and hegemonic masculinities and that men's caring involvement entails a lot of complexity and identity negotiations. The authors also reflect on the issue of men in care in the neoliberal context of changes to both the labour market and masculinity, while discussing its transformative potential.
Keywords: care work; critical studies; gender studies; kritične študije; masculinities; men; moški; moškost; skrbstveno delo; študije spolov